Optimization Estimation Parameters of COCOMO Model II Through Genetic Algorithm - Khatoon, Arfiha; Kaur, Rupinder (International Journal of Computer Sciences and Engineering, 2025)
Software cost estimation is very important in software project management.a major cause of failure of many software projects is the lack of accurate and early estimation. However, irrespective of great deal of importance estimating the time and development cost accurately is still a challenge in software industry. It is used to predict the effort and time need to complete the project. The need of optimization comes in various approaches like genetic algorithm of COCOMO MODEL II for providing better effort estimates and reliability.